2015
DOI: 10.1002/jez.1922
|View full text |Cite
|
Sign up to set email alerts
|

Short‐day aggression is independent of changes in cortisol or glucocorticoid receptors in male Siberian hamsters (Phodopus sungorus)

Abstract: Testosterone mediates aggression in many vertebrates. In some species, aggression remains high during the non-breeding season (e.g., winter), when testosterone levels are low. In Siberian hamsters (Phodopus sungorus), we have demonstrated photoperiodic changes in aggression with hamsters housed in short, "winter-like" days displaying significantly more territorial aggression than long-day animals, despite low levels of testosterone. The mechanisms by which photoperiod regulates aggression, however, remain larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 65 publications
1
17
0
Order By: Relevance
“…One alternative hypothesis is that that marked ACTH‐induced increases in CORT concentrations attenuated the actions of elevated DHEA concentrations on aggression (Rendon et al, ). Prior studies have shown that elevated glucocorticoid levels can inhibit aggression in this and other species (Nock and Leshner, ; Leshner et al, ; Wingfield and Silverin, ; Scotti et al, ). Studies that block hormone‐specific enzymatic cascades allowing for differential release of DHEA and CORT concentrations in response to an ACTH challenge could distinguish these likely effects.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…One alternative hypothesis is that that marked ACTH‐induced increases in CORT concentrations attenuated the actions of elevated DHEA concentrations on aggression (Rendon et al, ). Prior studies have shown that elevated glucocorticoid levels can inhibit aggression in this and other species (Nock and Leshner, ; Leshner et al, ; Wingfield and Silverin, ; Scotti et al, ). Studies that block hormone‐specific enzymatic cascades allowing for differential release of DHEA and CORT concentrations in response to an ACTH challenge could distinguish these likely effects.…”
Section: Discussionmentioning
confidence: 82%
“…Increased aggression in short‐day‐like animals is blocked by bilateral adrenalectomy (which eliminates both adrenal steroids and catecholamines), but not demedullation (which eliminates catecholamines, leaving adrenal steroids intact) (Demas et al, ). Although these findings suggest a role for adrenal steroids, short‐day aggression is independent of both cortisol (CORT) levels and glucocorticoid receptor expression in hamsters (Scotti et al, ). In contrast, the adrenal androgen DHEA, a steroid that serves as a prohormone and can be converted to biologically active hormones (e.g., T and 17β–estradiol (E 2 )), appears to be a critical regulator of aggression in this and other species (Soma and Wingfield, ; Pradhan et al, ; Scotti et al, ; Rendon et al, ).…”
mentioning
confidence: 99%
“…These include pounces (lunges toward the playmates face or nape), pins (one animal on top, holding its playmate in the supine position), and boxing (both animals standing on their hind legs pushing or batting each other with their forepaws). Offensive aggressive behaviors in Siberian hamsters were typified by rapid strikes/bites typically directed toward the rump and genitals and vigorous chases that usually ended with the subordinate animal in the supine defensive posture [as in 10,11]. Unlike during playful pins, the dominant aggressor did not sustain contact during this supine posture.…”
Section: Resultsmentioning
confidence: 99%
“…GR expression is 4-fold greater than MR expression in the mPFC, a disproportionately greater ratio than in many other regions associated with the stress response (Cintra et al, 1994; Diorio et al, 1993), and, thus, the mPFC may play a differential role in stress-induced regulation of CORT or behavior, since the GR preferentially responds to elevated glucocorticoid levels. Yet, few studies have investigated the relation between mPFC GR and anxiety- and aggression-like behaviors (Lin et al, 2016; Scotti et al, 2015). Firstly, mPFC GR can modulate physiological stress through negative feedback on the HPA response (Akana et al, 2001; Diorio et al, 1993).…”
Section: Discussionmentioning
confidence: 99%